Constructivism and Science
304 p.
Keywords: The idea to produce the current volume was conceived by Jiirgen Mittelstrass and Robert E. Butts in 1978. Idealist philosophers are wrong about one thing: the temporal gap separating idea and reality can be very long indeed - even ten or so years! Problems of timing were joined by personal problems and by the pressure of other professional commitments. Fortunately, James Brown agreed to cooperate in the editing of the volume; the infusion of his usual energy, good judgement and good-natured promptness saved the volume and made its produc tion possible. Despite the delays, the messages of the papers included in the book have not gone stale. An extremely worthwhile exercise in international philosophical cooperation has come to fruition; the German constructivist philosophical position is here represented in papers in English that will make its contemporary importance available to a larger audience. The editors owe thanks to many persons. All involved in the project owe much to the interest and support of Nicholas Rescher, a friend of the undertaking from the time of its inception. My review of the translations was helped immensely by Andrea Purvis' careful copy editing of the typescript. Most of all, however, we owe gratitude and admiration for the tireless efforts on behalf of this enterprise to Jiirgen Mittelstrass.